Hubungan Pengetahuan, Motivasi dan Dukungan Keluarga dengan Tingkat Kepatuhan Menjalani Rehabilitasi Medik pada Pasien Pasca Stroke - Safira Putri Aulya; Retno Setyawati; Suyanto Suyanto (Lembaga Pengembangan Kinerja Dosen, 2025)
Stroke occurs due to a blockage or rupture of blood vessels in the brain, leading to tissue damage and functional impairment, which can result in death. Post-stroke patients require long-term medical rehabilitation for recovery and relapse prevention. However, patient compliance with rehabilitation is often low. Factors influencing compliance include knowledge about rehabilitation, motivation to recover, and family support, all of which play a crucial role in the success of rehabilitation.This study aims to analyze the relationship between knowledge, motivation, and family support with the compliance of post-stroke patients in undergoing medical rehabilitation. This research employs a quantitative approach with a cross-sectional design, using total sampling of 44 respondents. Data were collected through questionnaires and statistically analyzed using the Somers’ d test. The study results showed that among the 44 respondents, 72.5% had a moderate level of knowledge, 79.5% had high motivation, 52.3% received moderate family support, and 90.9% demonstrated a high level of compliance. The correlation between knowledge and compliance was 0.490 with a p-value of 0.021, while the correlation between motivation and compliance was 0.600 with a p-value of 0.034. There is a significant relationship between knowledge, motivation, and family support with the compliance of post-stroke patients in undergoing medical rehabilitation.